Lipocalin-2 controls neuronal excitability and anxiety by regulating dendritic spine formation and maturation - Mucha, Mariusz (National Academy of Sciences, 2011)
Psychological stress causes adaptive changes in the nervous system directed toward maintaining homoeostasis. These biochemical and structural mechanisms regulate animal behavior, and their malfunction may result in various forms of affective disorders. Here we found that the lipocalin-2 (Lcn2) gene, encoding a secreted protein of unknown neuronal function, was up-regulated in mouse hippocampus following psychological stress. Addition of lipocalin-2 to cultured hippocampal neurons reduced dendritic spine actin's mobility, caused retraction of mushroom spines, and inhibited spine maturation. These effects were further enhanced by inactivating iron-binding residues of Lcn-2, suggesting that they were facilitated by the iron-free form of Lcn-2. Concurrently, disruption of the Lcn2 gene in mice promoted stress-induced increase in spine density and caused an increase in the proportion of mushroom spines. The above changes correlated with higher excitability of CA1 principal neurons and with elevated stress-induced anxiety in Lcn-2(−/−) mice. Our study demonstrates that lipocalin-2 promotes stress-induced changes in spine morphology and function to regulate neuronal excitability and anxiety.